Engineered BMSCs-Derived Exosomal miR-542-3p Promotes Cutaneous Wound Healing - Xiong, Qing-Hua; Zhao, Lei; Wan, Guan-Qun; Hu, Yun-Gang; Li, Xiao-Lin (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: The healing of cutaneous wounds requires better strategies, which remain a challenge. Previous reports indicated that the therapeutic function of mesenchymal stem cells is mediated by exosomes. This work demonstrated the regenerative effects of engineered BMSCsderived Exosomal miR-542-3p in skin wound mouse models. Methods: Bone marrow mesenchymal stem cells (BMSCs) -derived exosomes (BMSCs-Exos) were isolated by ultracentrifugation and identified by Transmission Electron Microscope (TEM) and Nanoparticle Tracking Analysis (NTA). BMSCs-Exo was loaded with miRNA-542-3p by electroporation. We explored the effects of miRNA-542-3p-Exo on the proliferation and migration of Human Skin Fibroblasts (HSFs)/Human dermal microvascular endothelial cells (HMECs). In addition, The angiogenesis of HMECs was detected by Tube formation assay in vitro. The effects of miRNA-542-3p-Exo in the skin wound mouse model were detected by H staining, Masson staining, and immunofluorescence analysis. We assessed the effect of miRNA-542-3p-Exo on collagen deposition, new blood vessel formation, and wound remodeling in a skin wound mouse model. Results: MiRNA-542-3p-Exos could be internalized by HSFs/HMECs and enhance the proliferation, migration, and angiogenesis of HSFs/HMECs in vitro and in vivo. The protein expression of collagen1/3 was significantly increased after miRNA-542-3p-Exo treatment in HSFs. In addition, the local injection of miRNA-542-3p-Exo promoted cellular proliferation, collagen deposition, neovascularization, and accelerated wound closure. Conclusion: This study suggested that miRNA-542-3p-Exo can stimulate HSFs/HMECs function. The treatment of miRNA-542-3p-Exo in the skin wound mouse model significantly promotes wound repair. The therapeutic potential of miRNA-542-3p-Exo may be a future therapeutic strategy for cutaneous wound healing.
Keywords: Bone marrow mesenchymal stem cells (BMSCs)